Anti-inflammatory and anti-apoptotic effect of zingiberene on isoproterenol-induced myocardial infarction in experimental animals. (June 2021) - Li, Jianwei; Thangaiyan, Radhiga; Govindasamy, Kanimozhi; Wei, Jianxia
This study aimed to investigate the antihyperlipidemic and anti-inflammatory effect of zingiberene (ZBN) on isoproterenol-(ISO) induced myocardial infarction in rats. ZBN (10 mg/kg b.wt.) was orally administered to rats for 21 days and ISO (85 mg/kg b.wt.) was subcutaneously injected into the rats at 24 h intervals for the last 2 consecutive days. We observed increased serum creatine kinase, creatine kinase-MB, cardiac troponin T, and I levels in ISO-treated MI rats. Conversely, ZBN oral administration significantly prevented in cardiac marker enzyme activities in ISO-mediated rats. We also noticed that ZBN oral administration prevented ISO-induced expression of lipid peroxidative markers, total cholesterol, triglycerides, phospholipids, free fatty acids, very-low-density lipoprotein cholesterol (VLDL-C), low-density lipoprotein cholesterol (LDL-C) to the normal basal level. Furthermore, ZBN restored ISO-mediated antioxidant status, increased level of high-density lipoprotein cholesterol (HDL-C), and tissue phospholipids to the near-normal levels. Besides, ZBN pre-treatment significantly reduced the level of inflammatory markers (TNF-α, IL-6, NF-κB, and IL-1β) in ISO-induced MI in rats. We noticed that ZBN pretreatment inhibited the pro-apoptotic proteins Bax and cytochrome c and increased the Bcl-2 expression in ISO induced rats. The gene expression profiling by qRT-PCR array illustrates that ZBN treatment prevents the ISO mediated activation of cardiac markers, inflammatory, and fibrosis-related genes in the heart tissue. Taken together, pre-treatment with ZBN attenuated ISO-induced MI resolved exhibits the anti-inflammatory and antiapoptotic effect.